Synthesis of Fluorite (CaF2) Crystal from Gypsum Waste of Phosphoric Acid Factory in Silica Gel - Mohammad Misbah Khunur; Andri Risdianto; Siti Mutrofin; Yuniar Ponco Prananto (Bulletin of Chemical Reaction Engineering & Catalysis, 2012)
This paper report the synthesis and characterization of fluorite single crystal prepared from gypsum waste of phosphoric acid production in silica gel. Instead of its high calcium, gypsum was used to recycle the waste which was massively produces in the phosphoric acid production. The gypsum waste, the raw material of CaCl2 supernatant, was dissolved in concentrated HCl and then precipitated as calcium oxalate (CaC2O4) by addition of ammonium oxalate. The CaCl2 was obtained by dissolving the CaC2O4 with HCl 3M. The crystals were grown at room temperature in silica gel and characterized by AAS, FTIR and powder XRD. The optimum crystal growth condition, which is pH of gel, CaCl2 concentration and growth time, were investigated. The result shows that at optimum condition of pH 5.80, CaCl2 concentrations of 1.2 M, and growth time of 144 hours, colorless crystals with the longest size of 3 mm, were obtained (72.57%). Characterization of the synthesized crystal by AAS indicates that the obtained crystal has high purity. Meanwhile, analysis by FTIR spectra shows a Ca–F peak at 775 cm-1, and powder-XRD analysis confirms that the obtained crystal was fluorite (CaF2). © 2012 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)